ChemInform Abstract: Antiinflammatory Alkaloid Glycoside and Quinoline Alkaloid Derivates from the Stems of Clausena lansium. Issue 7 (January 2016) - Liu, Jie; Li, Chuang‐Jun; Ni, Lin; Yang, Jing‐Zhi; Li, Li; Zang, Cai‐xia; Bao, Xiu‐Qi; Zhang, Dan; Zhang, Dong‐Ming
Abstract: Six new alkaloid glycosides, clausenasides A‐F, and two novel quinoline alkaloids, clausenasides G‐H, are isolated along with ten known compounds from the stems of C.